1993
DOI: 10.1101/gad.7.9.1737
|View full text |Cite
|
Sign up to set email alerts
|

mRNA destabilization triggered by premature translational termination depends on at least three cis-acting sequence elements and one trans-acting factor.

Abstract: Nonsense mutations in a gene can accelerate the decay rate of the mRNA transcribed from that gene, a phenomenon we describe as nonsense-mediated mRNA decay. Using amber (UAG) mutants of the yeast PGK1 gene as a model system, we find that nonsense-mediated mRNA decay is position dependent, that is, nonsense mutations within the initial two-thirds of the PGKl-coding region accelerate the decay rate of the PGK1 transcript ~<12-fold, whereas nonsense mutations within the carboxy-terminal third of the coding region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

16
349
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(366 citation statements)
references
References 54 publications
16
349
0
Order By: Relevance
“…The yeast UPF1 gene has been shown to be essential for NMD, deletion of which restores wt decay rates to nonsensecontaining mRNA transcripts. 10 We therefore generated a upf1∆ strain of S. cereVisiae and compared the UAA incorporation efficiency in this strain to the wt strain.…”
mentioning
confidence: 99%
“…The yeast UPF1 gene has been shown to be essential for NMD, deletion of which restores wt decay rates to nonsensecontaining mRNA transcripts. 10 We therefore generated a upf1∆ strain of S. cereVisiae and compared the UAA incorporation efficiency in this strain to the wt strain.…”
mentioning
confidence: 99%
“…Mutations in the UPF genes were isolated as allosuppressors of a his4 frameshift allele (17,43). Subsequent studies demonstrated that strains harboring the upf1 and upf3 alleles, and as shown in more recent studies also upf2, lead to the selective stabilization of nonsense-containing mRNAs without affecting the decay rates of most other mRNAs (16,26,42,43,56). The UPF1 and UPF2 genes have been cloned and sequenced (16,25,43).…”
mentioning
confidence: 99%
“…Our results, as well as work from other laboratories, strongly indicate that the processes of mRNA turnover and translation are intimately linked and that understanding of this relationship is critical in elucidating the mechanism of mRNA decay (2, 5, 9, 11, 15, 21, 23, 29-31, 41, 53, 55-59, 76). The role of translation in determination of mRNA decay rates is direct, and, for certain instability elements identified in protein coding regions and 3Ј untranslated regions (3Ј-UTRs), translation of the protein coding region must occur in order for them to function (2,11,15,21,23,29,41,53,60,66,76).One clear example of the relationship between translation and mRNA decay is the observation that nonsense mutations in a gene can reduce the abundance of the mRNA transcribed from that gene in a process we term nonsense-mediated mRNA decay (55,56,58). Reduced mRNA levels or decreased stabilities of nonsense-containing transcripts have been observed in both prokaryotes and eukaryotes (6-8, 13, 14, 18, 20, 22, 42, 44-47, 51, 54, 56, 71, 75).…”
mentioning
confidence: 99%
See 2 more Smart Citations